Thymol: Use in Antimicrobial Packaging - Guarda-Moraga, A; Galotto-Lopez, M; Torres-Mediano, A; Lopez de Dicastillo-Bergamo, A (Elsevier Inc., 2016)
Nowadays, there has been a change in the paradigm of food packaging. It is expected that food packaging will be able to enhance food quality, shelf life, and food safety. In this sense, active packaging (AP) has arisen as an alternative to provide food packaging protection.Within the different AP systems, great attention has been focused on antimicrobial (AM) packaging, as these methods act on the food surface where the microorganisms grow. Essential oils and different phenolic components are the most promising active AM components to be included in an AP. In the present chapter, the physicochemical properties of thymol are reviewed, along with its use as an AM compound for active food packaging, including the different incorporation mechanisms in the packaging matrix and its kinetic release. © 2016 Elsevier Inc. All rights reserved.